2017
DOI: 10.1016/j.combustflame.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling study of the pyrolysis and combustion of 2-methyl-tetrahydrofuran

Abstract: Saturated cyclic ethers are being proposed as next-generation bio-derived fuels. However, their pyrolysis and combustion chemistry has not been well established. In this work, the pyrolysis and combustion chemistry of 2-methyl-tetrahydrofuran (MTHF) was investigated through experiments and detailed kinetic modeling. Pyrolysis experiments were performed in a dedicated plug flow reactor at 170 kPa, temperatures between 900 and 1100K and a N 2 (diluent) to MTHF molar ratio of 10. The combustion chemistry of MTHF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 57 publications
1
50
0
Order By: Relevance
“…However, the quantitative agreement is poor for most species. Then, De Bruycker et al [146] presented another 2-MTHF kinetic model, developed with the help of new advanced theoretical calculations. The authors segment the new model into three main mechanisms: a primary mechanism, covering the oxidation and pyrolysis of 2-MTHF and its radicals; a base mechanism, capturing the oxidations and pyrolysis of small oxygenates and hydrocarbons; and a secondary mechanism, focusing on 2-MTHF decomposition products.…”
Section: Detailed Chemical Kinetic Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the quantitative agreement is poor for most species. Then, De Bruycker et al [146] presented another 2-MTHF kinetic model, developed with the help of new advanced theoretical calculations. The authors segment the new model into three main mechanisms: a primary mechanism, covering the oxidation and pyrolysis of 2-MTHF and its radicals; a base mechanism, capturing the oxidations and pyrolysis of small oxygenates and hydrocarbons; and a secondary mechanism, focusing on 2-MTHF decomposition products.…”
Section: Detailed Chemical Kinetic Modelsmentioning
confidence: 99%
“…The pyrolysis of 2-MTHF was recently investigated by De Bruycker [146] in a plug flow reactor at a pressure of 170 kPa, temperatures of 900-1100 K and an N 2 /2-MTHF molar ratio of 10. The results indicated that the main pathway for decomposition is by cleavage of the CH 3 group and ring opening to 4-penten-1-ol.…”
Section: Experimental Chemical Kinetic Studiesmentioning
confidence: 99%
See 3 more Smart Citations